Espalhamento Raman polarizado em cristais de L-arginina.HCl:H2O e estudo da L-arginina.2H2O sob altas pressões e sob altas temperaturas - Gonçalves, Ricardo Oliveira (2012)
The objective of this Thesis is the study through Raman spectroscopy of two crystals containing amino acid L-arginine: L-arginine monohydrated hydrochloride (LARHCL) and L-arginine dihidrated (LARDH). In the first part of the work it was presented structural and vibrational aspects of LARHCL and LARDH, particularly the distribution of normal modes in terms of the irreducible representations of factor groups C2 and D2, respectively. The room temperature normal modes of LARHCL observed through polarized Raman spectroscopy using nine different scattering geometries was presented. Using ab initio calculations it was possible to tentatively assign the Raman-active normal modes of LARHCL. In another part of the work it is presented the analysis of Raman spectra of LARDH under several temperature and pressure conditions. It was studied the normal modes of LARDH crystal through Raman spectroscopy in the range between 30 oC and 200 oC. From this study it was observed the occurrence of anomalies in the Raman spectra, such as change in the curves dw/dT related to modes of low frequency (at about 45 oC), as well as the fact that, starting from 50 oC, in a heating process, some bands decrease intensity. Such a picture suggested that LARDH crystal undergoes a phase transition between 45o and 50oC. Also, it was possible to note that the spectra recorded between 45o and 60oC were different from those recorded for T < 45oC and for T > 60oC suggesting the coexistence of phases in this temperature interval. Another hypothesis was that the crystal undergoes a phase transition at 45oC, remaining in this phase up to the temperature of 60oC. Additionally, it was possible to perform thermal analysis measurements, differential thermal analysis (DTA) and thermogravimetric analysis (TG). From the DTA it was observed that between 45o and 50oC begins an endothermic event that is observed up to 84oC. A second endothermic event begins and remains up to 109oC. By using TG data it was possible to understand that these two events are related to water that left the crystal, although a small quantity remains in the crystal, as pointed out by Raman spectroscopy. In the final part of the work LARDH crystal under high pressure conditions was studied up to 8 GPa. From this study, in particular the analysis of external modes, it was revealed that the crystal undergoes a phase transition at ~ 2,5 GPa. However, for pressures between 2,5 and 8,0 GPa no additional phase transition was observed, pointing to a great stability of the crystal when compared with other amino acid hydrated crystals. Additionally, there is no great change in the internal mode region of the Raman spectrum, suggesting that the phase transition undergone by LARDH under high pressure conditions can be classified as a conformational one.